Data rescue in manuscripts: a hydrological modelling study example. Issue 5 (3rd April 2020) - Yu, Xuan; Lamačová, Anna; Shu, Lele; Duffy, Christopher; Krám, Pavel; Hruška, Jakub; White, Tim; Lin, Kairong
ABSTRACT: Recently, data statements have been required in hydrological manuscripts. Authors are usually confused by different data management policies. Thus, a frequent response is to write down "data available upon request from the corresponding author". Such a simplified response may lead to dormancy or permanent loss of data. We present an example of data management from a published hydrological modelling study. We started from figures with complete scientific stories in the publication and traced backwards to find relevant source data through workflows (linking). In this manner, the source data can be identified (archiving) and preserved (hosting). Such simple practices of data linking, archiving and hosting can rescue data and require only limited effort by the authors. We suggest that this data rescue process(es) should become routine in the scientific publication process. The data rescued with workflows can significantly improve the research transparency and reusability, which leads to a fairer and more open culture in hydrology.